2021
DOI: 10.1186/s12891-021-04009-x
|View full text |Cite
|
Sign up to set email alerts
|

Is early full weight bearing safe following locking plate ORIF of distal fibula fractures?

Abstract: Background In the modern western world appraisal of economical points such as treatment and disability after trauma present a financial burden. In this context open reduction internal fixation techniques allowing for early full weight bearing might not only improve the clinical outcome but also shorten the period of disability in working life. The aim of the study was to analyze whether ORIF of ankle fractures using either a standard semitubular plate or a new polyaxial locking plate system res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Of the 8 studies comparing weight-bearing interventions, 3 reported better primary outcomes in the early weight-bearing group compared with the late weight-bearing groups, all of which measured outcomes over the short-term (2–12 weeks). 65,66,68 The other studies showed no differences or similar outcomes across groups. 22,62–64,67 Importantly, the 4 studies examining long-term outcomes of 6 or 12 months showed similar outcomes for both groups.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Of the 8 studies comparing weight-bearing interventions, 3 reported better primary outcomes in the early weight-bearing group compared with the late weight-bearing groups, all of which measured outcomes over the short-term (2–12 weeks). 65,66,68 The other studies showed no differences or similar outcomes across groups. 22,62–64,67 Importantly, the 4 studies examining long-term outcomes of 6 or 12 months showed similar outcomes for both groups.…”
Section: Resultsmentioning
confidence: 90%
“…Of all studies, 40 23–61 described their postoperative rehabilitation strategy but did not evaluate effectiveness and 15 20–22,62–73 focused on evaluating the effectiveness of the postoperative rehabilitation strategy. This section reports only those 40 studies that described their postoperative rehabilitation strategy, focusing on weight-bearing, immobilization, and other therapy administered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Open reduction and internal fixation (ORIF) has become the standard of care for displaced ankle FX in adults [ 13 , 14 ]. Several techniques for internal ankle fixation are commonly used, ranging from simple lag screw fixation to plate osteosynthesis with non-locking to locking screw systems up to biodegradable systems [ 15 , 16 , 17 , 18 , 19 , 20 ]. In this context, several studies in the common literature focus on intramedullary (IM) fixation of the distal fibula FX, fracture stabilization, and the appearance of soft tissue-related complications in the older population [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%